2017
DOI: 10.1186/s12915-017-0463-6
|View full text |Cite
|
Sign up to set email alerts
|

An elevated plus-maze in mixed reality for studying human anxiety-related behavior

Abstract: BackgroundA dearth of laboratory tests to study actual human approach-avoidance behavior has complicated translational research on anxiety. The elevated plus-maze (EPM) is the gold standard to assess approach-avoidance behavior in rodents.MethodsHere, we translated the EPM to humans using mixed reality through a combination of virtual and real-world elements. In two validation studies, we observed participants’ anxiety on a behavioral, physiological, and subjective level.ResultsParticipants reported higher anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
92
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(116 citation statements)
references
References 54 publications
9
92
2
Order By: Relevance
“…little is known about anxiety, especially its many human-specific cognitive-affective features. Indeed, many animal models of anxiety, such as the elevated-plus maze, have few analogues in humans 22 (although see Biederman et al 23 and Bach et al 24 ), and of course the impact of psychological therapies cannot be studied in animals. However, innovative approaches to study anxiety experimentally in humans have recently been developed.…”
Section: Ratmentioning
confidence: 99%
“…little is known about anxiety, especially its many human-specific cognitive-affective features. Indeed, many animal models of anxiety, such as the elevated-plus maze, have few analogues in humans 22 (although see Biederman et al 23 and Bach et al 24 ), and of course the impact of psychological therapies cannot be studied in animals. However, innovative approaches to study anxiety experimentally in humans have recently been developed.…”
Section: Ratmentioning
confidence: 99%
“…Behavioral avoidance tasks, where subjects anticipate a feared situation (e.g., anticipation of public speaking in social anxiety) is also a promising tool (188). For example, healthy controls and patients with social anxiety show distinct emotional responses and cognitive regulation to social threat compared to physical threat (185,189) and avoidance performance in a virtual elevated plus-maze is associated with symptom of acrophobia but not social anxiety or trait anxiety (190). This approach can also be extended to more specific symptoms such as emotional distraction by worries and intrusive thoughts (191).…”
Section: Sex and Developmental Changesmentioning
confidence: 99%
“…In rodents, intra-amygdala injection of benzodiazepines, which enhance the action of GABA by allosteric modulation of the receptor subtype A, has been shown to produce anxiolytic-like effects in a number of animal models of anxiety, including the elevated plus maze (EPM) (Green and Vale, 1992;Nunes-de-Souza et al, 2000;Pesold and Treit, 1995). Similarly, we have recently shown that systemic administration of the benzodiazepine Lorazepam in humans reduces anxiety-like behavior on a virtual reality version of the EPM (Biedermann et al, 2017). These results fit to previous studies, reporting that benzodiazepines reduces several types of threat responses in general, such as eye-blink startle responses towards darkness (Baas et al, 2002) and towards unpleasant pictures (Patrick et al, 1996).…”
Section: Introductionmentioning
confidence: 95%
“…46 of the 61 subjects took part in a virtual reality version of an EPM (Biedermann et al, 2017) before participating in this experiment (groups: Placebo, Yohimbine, Lorazepam). 15 subjects participated solely in this experiment and received no medication (no treatment control).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation